Grit blast assisted laser milling/grooving of metallic alloys - Li, L.; Kim, J.H.; Shukor, M.H.A. (2005)
Laser machining and milling of metallic alloys and ceramics have been previously carried out by either direct vaporisation or assist gas ejection of laser-melted materials. For certain metallic materials, due to the high viscosity of the materials in the molten state, it is difficult to achieve a clean cut. Recast and heat affected zones are normally formed. This paper reports a hybrid process combining a grit blasting and laser melting for the milling and grooving of stainless steel, mild steel and titanium alloys. The work shows that up to 100 increase in material removal rate and 15 reduction in the heat affected zone size can be achieved compared with a gas jet assisted laser machining process under the same operating conditions. Surface roughness has been reduced by 60. The effect of particle injection angle, direction on material removal rate is presented. A critical particle injection angle is established.